THE INFLUENCE OF EDUCATIONAL LEVEL, WORK EXPERIENCE AND COMPREHENSION OF ACCOUNTING INFORMATION SYSTEM ON FINANCIAL REPORT QUALITY - Fajar Adiyanto (Jurnal Akuntansi Indonesia, 2018)
This study is conducted to: 1) test and analyze the influence of educational level on financial report quality; 2) test and analyze the influence of work experience on financial report quality; 3) test and analyze the influence of accounting information system on financial report quality. Population in this study is all employees employed in district financial department in Surakarta with the sample amounted of 30 employees. Data analysis method is multi-linear regression. Results of hypothesis analysis showed that work experience (H2) and accounting information system comprehension (H3) have influence on financial report quality, and the educational level (H1) variable has no influence on financial report quality.Keywords: Educational level, work experience, accounting information system comprehension, financialreport quality.